WOMEN WHO WORK TOO MUCH : BREAK FREE FROM TOXIC PRODUCTIVITY & FIND YOUR JOY - Thomas, Tamu (Baker Street, London : HAY HOUSE, 2024)
"We have been conditioned into believing our value is in what we do rather than who we are. Do you find yourself saying 'yes' because you were never taught how to say 'no'? Are you working all hours of the day, but not feeling good about your achievements, amplifying your perceived mistakes or weaknesses? Many of us believe that to be our best selves we should do more, but the result is often stress, burnout, and disillusionment. This book offers a healing hand to help you step out of the same old patterns of using success or overworking as a source of self-validation. For women, work doesn't stop in the workplace. There is a huge load at home that still falls to women-- whether looking after children, caring for aging parents, or simply taking the reins of running the household. This is a book for women who work too much. It is for women who are ready to hear the wake-up call coming from within: coming from their frazzled nervous system, from that sense of underlying anxiety they have learnt to normalize over the years, and from an inner knowing that-- just maybe-- it doesn't have to be this way." -- Amazon.com
Bibliography: pages 251-257.
Keywords: Women employees; Work-life balance; Women -- Employment